P-497 Men's attitude towards two fertility education interventions and preferences for future fertility awareness initiatives. (30th June 2022) - Schmidt, L; Larsen, C; Louise, M; Sylvest, R; Koert, E
Abstract: Study question: What are men's preferences for communication of fertility information and how to target prevention efforts to promote men to make informed decisions regarding family formation? Summary answer: Men preferred fertility education interventions to use positive language to create new knowledge, include personal stories as conversation starters, and be provided in different formats. What is known already: The far majority of men in Denmark wants to become fathers; however, 20% of 50-year-old men are childless compared to 12% among women. Around 40% of men in Denmark have reduced semen quality. Previous studies have found that men have insufficient knowledge about fertility, infertility and associated risk factors, and that men want to receive more information about fertility when they are young. Only few intervention studies have been performed about how to increase men's and women's fertility knowledge, and even fewer studies have focused only on men. Study design, size, duration: Qualitative focus group discussions with 13 men assigned into five focus groups were carried out. Two interventions were introduced; an episode from the podcast "Actually you don't have to wait that long" about two couples who have become parents in their mid-twenties, and an informational poster developed by The International Fertility Education Initiative was shown during the group discussions. The interviews took place online over Zoom in January 2021. Interviews ranged in average 91 minutes. Participants/materials, setting, methods: All participants were recruited through Facebook and social networks. The interviewed men were young, childless aged 25-32 in a committed relationship and all residents in Copenhagen, Denmark. Focus group questions were semi-structured and examined the men's reactions to the podcast and poster and preferences for communication of fertility information. The focus group discussions were recorded, anonymized and transcribed. Data were analyzed using Graneheim and Lundman's method of qualitative content analysis. Main results and the role of chance: The overall themes were: "Poster: source of information", "Podcast: report from the lived life" and "Information targeting men". The men's reactions to the poster and podcast were categorized into the sub-themes benefits and critiques and suggestions. Benefits of the poster was that it included important knowledge and was relevant to a large target group. Critiques were that it had too much information and lacked the emotional aspect of family formation. They wished for more positive languaging and communication about the fertility information on the poster. The benefit of the podcast was the use of personal stories to highlight the emotional aspect of family formation which was a conversation starter for partners. Critiques were that some men found the personal stories unrelatable and believed it didn't contribute new knowledge. They suggested to include couples with fertility problems with an expert. According to men, future interventions should focus on how information is communicated. It should be factual, include humor and not be negative or shameful. Different formats to provide fertility information including TV-programs, podcasts, and social media interventions should be used to reach the most men in different ways. They also suggested fertility information should be included in sexual education in school. Limitations, reasons for caution: All men were residents of the capital city Copenhagen, and men with a short education were underrepresented. Therefore, our results may not represent the opinions of all men aged 25-32 years in Denmark. Wider implications of the findings: In the future fertility awareness campaigns should be developed in cooperation with the target group together with clinicians, and concurrent intervention studies on the developed methods should be performed. In all probability, a mix of different interventions will be necessary to attain the desired effect to ensure long-lasting fertility awareness. Trial registration number: Not applicable